Efektivitas Jasa Konsultan Pajak Bagi Pengusaha UMKM dalam Meningkatkan Kepatuhan Kewajiban Perpajakan - Aulia Fernandia Novana Putri; Dianing Widya Kusumastuti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, particularly in contributing to gross domestic product and employment creation. Nevertheless, the level of tax compliance among MSMEs remains relatively low. This condition is influenced by limited tax literacy, complex tax regulations, and constraints in administrative capacity and human resources, which hinder MSMEs from fulfilling their tax obligations accurately and sustainably. In this context, tax consultant services are considered a viable solution to assist MSMEs in overcoming technical and regulatory challenges related to taxation. This study aims to analyze the effectiveness of tax consultant services in improving MSMEs’ tax compliance. The research employs a qualitative descriptive approach. A case study was conducted at PT XYZ, a Micro, Small, and Medium Enterprise engaged in retail trading and computer and printer repair services located in Surakarta City. Research data were obtained through in-depth interviews with internal company personnel and external tax consultants, observation of tax administration practices, and documentation of relevant tax records. The collected data were analyzed using qualitative data analysis techniques, including data reduction, data presentation, and conclusion drawing. The results indicate that tax consultant services are effective in enhancing both formal and material tax compliance among MSMEs. This effectiveness is reflected in improved understanding of tax regulations, more orderly tax administration, timely tax reporting, and accurate tax calculations. However, the level of effectiveness is influenced by the intensity of assistance provided and MSMEs’ perceptions regarding the cost of tax consulting services. This study provides empirical evidence on the strategic role of tax consultants in supporting sustainable tax compliance among MSMEs.